Challenges to civil rights guarantees in India - Noorani, A.G. (New Delhi, 2012)
This volume consisting of nine essays thoroughly examines the status of civil rights guarantees as enshrined in the Constitution of India. Discussing the contemporary social and political issues, and their handling by the state, it foregrounds different challenges faced by the civil rights framework in India. The essays elaborately analyse civil and criminal justice system, and cover topics, such as the death penalty, counter-terrorism activities, anti conversion laws, and freedom of speech. The work also brings out the complex relationship between curtailment of democratic tools of protest and enjoyment of civil rights
Keywords: Civil rights-India